Vinegar-Baked Radix Bupleuri Regulates Lipid Disorders via a Pathway Dependent on Peroxisome-Proliferator-Activated Receptor-α in High-Fat-Diet-Induced Obese Rats. (27th December 2011) - Tzeng, Thing-Fong; Lu, Hung-Jen; Liou, Shorong-Shii; Chang, Chia Ju; Liu, I-Min
Abstract : The aim of this study was to investigate the antiobesity and antihyperlipidemic effects of vinegar-baked Radix Bupleuri (VBRB) on high-fat diet- (HFD-) induced obese rats. After being fed HFD for two weeks, rats were dosed orally with VBRB or fenofibrate, once daily for further twelve weeks. VBRB (1.0 g kg −1 per day) produced effects similar to fenofibrate (100 mg kg −1 ) in reducing body weight (BW) gain, visceral fat-pad weights, plasma lipid levels, as well as hepatic TG and cholesterol content of HFD-fed rats. VBRB also lowered hepatic lipid droplet accumulation and the size of epididymal adipocytes in HFD-fed rats. VBRB and fenofibrate reversed the HFD-induced downregulation of hepatic peroxisome proliferator-activated receptor (PPAR)α. HFD-induced reductions in the hepatic levels of acyl-CoA oxidase (ACO) and cytochrome P450 isoform 4A1 (CYP4A1) proteins were reversed by VBRB and fenofibrate. The elevated expression of hepatic sterol regulatory element binding proteins (SREBPs) in HFD-fed rats was lowered by VBRB and fenofibrate. The results of this study show that VBRB suppresses BW gain and body fat accumulation by increasing fatty acid oxidation, an effect which is likely mediated via upregulation of PPARα and downregulation of SREBP expression in the liver of HFD-fed rats.